2017
DOI: 10.1186/s13634-017-0469-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-pulse modulation recognition using short-time ramanujan Fourier transform spectrogram

Abstract: Intra-pulse modulation recognition under negative signal-to-noise ratio (SNR) environment is a research challenge. This article presents a robust algorithm for the recognition of 5 types of radar signals with large variation range in the signal parameters in low SNR using the combination of the Short-time Ramanujan Fourier transform (ST-RFT) and pseudo-Zernike moments invariant features. The ST-RFT provides the time-frequency distribution features for 5 modulations. The pseudo-Zernike moments provide invarianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Traditional recognition methods of feature extraction can be divided into two parts: feature extraction and classification. For feature extraction, scholars have proposed feature extraction methods based on fractional Fourier transform [6], [8], short-time Ramanujan Fourier transform [7], integrated quadratic phase function [8] and other feature extraction methods. However, the generalization performance and anti-noise performance of these methods are poor, and it is difficult to meet the needs of current radar intra-pulse modulation recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional recognition methods of feature extraction can be divided into two parts: feature extraction and classification. For feature extraction, scholars have proposed feature extraction methods based on fractional Fourier transform [6], [8], short-time Ramanujan Fourier transform [7], integrated quadratic phase function [8] and other feature extraction methods. However, the generalization performance and anti-noise performance of these methods are poor, and it is difficult to meet the needs of current radar intra-pulse modulation recognition.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed method based on EC-STFT and RDBN achieves a higher recognition rate than other radar emitter intra-pulse signal recognizing methods. In the simulations, we selected four recognition methods with similar study objects and constraints: STFT + SCDAEs [ 2 ], 3DDF + TL [ 21 ], TFI + CNN [ 22 ] and ST-RFT + PZMs [ 23 ]. These four methods all focus on radar emitter intra-pulse signal recognition with five to seven types.…”
Section: Simulations and Discussionmentioning
confidence: 99%
“…The TFD is a good method to study radar emitter intro-pulse signals. In [ 21 , 22 , 23 ], STFT, WVD and CWD were improved and applied to recognition work. In [ 3 ], we combined STFT with CNN to complete the recognition task and found that the noise could disorder the two dimensional distribution, which resulted in a low recognition rate of less than −3 dB.…”
Section: The Proposed Recognition Methods Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, non-uniform sampling caused by instability of electronic clock, reconstruction of computed tomography image, radar signal processing, etc. The problem of equally spaced sampling [1] .…”
Section: Introductionmentioning
confidence: 99%